Kinesthetic learning approach and process skills in science laboratory activities - Legaspino, Daphne; Yanong, Chylsea Gelyn; Wenceslao, Noemi; Anino, Rosejhon Joy; Tolin , Margarito; Caparas, Jhonnelle Tien (Journal of Social, Humanity, and Education, 2024)
Abstract Purpose: This study aimed to determine the influence of students’ kinesthetic learning approach on e-learning process skills in a science laboratory during the COVID-19 Pandemic. Research methodology: This quantitative study utilized a descriptive-correlational approach. This study administered two sets of survey questionnaires: an adapted survey questionnaire and a validated researcher-made questionnaire to determine the level of kinesthetic learning approach on e-learning and the level of students’science process skills. Mean and Pearson’s r were the statistical tools used in this study. Further, there is no significant relationship between the kinesthetic learning approach of students and their science process skills. Results: The findings showed that the level of kinesthetic learning approach of the students on e-learning in the new normal education is average and contributory to these findings were critical thinking, collaborative skills, creativity and innovation, and technology application. Meanwhile, the level of students’ process skills in performing laboratory activities in science is high; specifically, the indicator basic science process skills are high and integrated science process skills are high. Limitations: Using a complete enumeration technique, 128 Grade 9 students during the school year 2021-2022 were selected based on the criterion that they experienced conducting science laboratory activities in a new normal setting. Contribution: The findings of the study were deemed significant to students, teachers, school administrators, and future researchers because they highlighted the need to align learning approaches to the learning needs of students, specifically in the science learning process, for them to actively engage and participate in learning. Keywords: Kinesthetic learning approach to e-learning, science process skills, science, grade 9 students, quantitative study descriptive-correlational approach. How to Cite: Legaspino, D., Yanong, C. G. F., Anino, R. J. C., Wenceslao, N., Tolin, M. C., & Caparas, J. T. S. (2024). Kinesthetic learning approach and process skills in science laboratory activities. Journal of Social, Humanity, and Education/ Vol4No4, 277-297.